2x-4=3x-11 so add 4 to 11 and that’s -7 then subtract 2x from 3x so that’s 1x so 1x divides by -7 equals -7 so x=-7
X² +18x = 0
To complete the square we are going to use formula a² +2ab +b² = (a+b)²
x² +2*9*x = 0
x² +2*9x+9² = 9²
(x+9)² = 9²
√(x+9)² = +/-√9²
x+9 = 9, or x+9 = -9
x=0, or x= - 18
The equation could be solved different way
x² +18x = 0
x(x+18) = 0
x=0 or x+18=0
x=0 or x=-18
Factor out the GCF first
3(2x² - x - 10)
3(2x - 5)(x + 2)
Answer:
y- intercept = - 10 or (0, - 10 )
Step-by-step explanation:
to find the y-intercept, that is where the graph crosses the y- axis let x = 0 in the equation
f(0) = -
(3)³ - 1
= -
× 27 - 1 = - 9 - 1 = - 10